Comparison of Extraction Methods for 11-Nor-Delta-9-Tetrahydrocannabinol-9-Carboxylic Acid (Thc-Cooh) in Urine Samples Prior to GC-MS Analysis - Yayayürük, Aslı Erdem; Girgin, Selim; Vuruk, Serkan; Güler, Ülkü; Güngör, Melike; Bostancı, Halil İbrahim; Akgür, Serap Annette (The Bulletin of Legal Medicine, 2016)
Objective: Marijuana is the most widely used illegal substance in the world. The target analyte for cannabinoids analysis in urine is THC-COOH. The most widely used sample preparation methods for THC-COOH are liquid-liquid extraction (LLE) and solid phase extraction (SPE). The aim of this work is to compare the extraction methods (LLE and SPE) for (±)-ll-nor-9-carboxy-A9-THC ÇTHC-COOH) for synthetic urine samples (n=80) prior to Gas Chromatography Mass Spectrometry (GC-MS) analysis. In addition, a method validation was conducted in terms of reproducibility, selectivity, accuracy, precision and linearity.Materials and Methods: (±) -1 l-nor-9-carboxy-A ’-THC and (±) -ll-nor-9-carboxy-A9-THC-D3 (as the internal standard) were used in the studies. Toxi tube B and Clean Screen THC cartridges were used for LLE and SPE, respectively. BSTFA with 1% TMCS were used in the derivatization step. The analysis is performed with Thermo Finnigan Trace GC-MS. Minitabll was used in statistical evaluations.Results: The limit of detection (LOD) was found to be 2 pg/L. All recovery values were >90% with RSD values
Keywords: tch-cooh; liquid-liquid extraction; solid phase extraction; urine; gas chromatography mass spectrometry